Identification of Key Drivers for Municipal Utility Performance - Jasmin Alsaied (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
This report explores the various performance indicators for municipal electric utilities and the greatest impact financial investments can make for improving these indicators. A literature search provided key detail about performing an analysis that would prove useful to utilities. The analysis identifies key performance indicators that allowed for the most prudent of investments. Data mining techniques and statistical analyses were performed on data sets concerning the 51 North Carolina municipal electric utilities to identify several key ratios and performance indicators that have the greatest impact on cost of service, system reliability, and customer satisfaction. Statistical analyses were used to determine which investments optimized these outcomes. No other studies on the statistical significance of municipal electric utility performance indicators were identified in our literature search.
Keywords: municipal utility performance; cost analysis of service; electric reliability